TH2.2: Framework for incorporating Gender Equality and Social Inclusion (GESI) elements in Climate Information Services (CIS) - Mapedza, Everisto D.; Huyer, Sophia; Chanana, Nitya; Rose, Alison; Jacobs-Mata, Inga; Mudege, Netsayi N.; Homann-Kee Tui, Sabine; Gbegbelegbe, Sika; Nsengiyumva, Gloriose; Mutenje, Munyaradzi; Nohayi, Nina (International Water Management Institute, 2022)
This paper proposes a Gender Equality and Social Inclusion (GESI) Framework for incorporating Climate Information Services which is increasingly becoming important due to climate change and climate variability. Our paper understands gender as a socially constructed definition of women and men. Gender inequalities seem to be pervasive in that, even with the introduction of new agricultural and climate information technologies, the gendered fault lines still appear within the new technological settings. Such gendered technological inequalities can be traced back to as early as the 1960s, where it was clear that technological solutions are grounded within the society in which they are embedded. Unless women are intentionally included in the design and development of agricultural technologies, there is a high risk that women will not benefit from agricultural innovations meant to ameliorate the impact of climate change and climate variability. According to Conway's law, any technology reflects the values of its creator. Therefore, it is of paramount importance to understand the values of those who create technological solutions and innovations. Our proposed framework has five indicators which are namely: Gender targeting by design, Sex disaggregated data collection, analysis of sex-disaggregated data, dissemination technological options and ongoing gender monitoring, and empowerment evaluation. The five indicator domains are further complemented by their respective assumptions. The five indicator domains are applied in the context of three development interventions which are namely agricultural data hub, Climate Information Services Training, and Flood and Drought Indicators which are all being implemented in Zambia as part of the Accelerating Impacts of CGIAR Climate Research for Africa Project (AICCRA) Project. The framework which is being applied in Zambia, is showing the importance of incorporating gender equality and social inclusion in the design, implementation and evaluation of climate information services.